2020
DOI: 10.1590/1678-4685-gmb-2018-0237
|View full text |Cite
|
Sign up to set email alerts
|

Resistance mutations of NS3 and NS5b in treatment-naïve patients infected with hepatitis C virus in Santa Catarina and Rio Grande do Sul states, Brazil

Abstract: Hepatitis C virus (HCV) infection is a worldwide health problem. Nowadays, direct-acting antiviral agents (DAAs) are the main treatment for HCV; however, the high level of virus variability leads to the development of resistance-associated variants (RAVs). Thus, assessing RAVs in infected patients is important for monitoring treatment efficacy. The aim of our study was to investigate the presence of naturally occurring resistance mutations in HCV NS3 and NS5 regions in treatment-naïve patients. Ninety-six anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The NS3 protease gene was successfully sequenced in all patients. Several reports demonstrated the presence of mutations associated with resistance to NS3 protease inhibitors; however, these studies were limited to GT1 and GT3 ( [7,8,9]. In the patients studied, we found the V170I mutation associated with resistance to NS3 protease inhibitors in three patients, of whom two were infected with GT4a+GT4o and one with GT4a.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The NS3 protease gene was successfully sequenced in all patients. Several reports demonstrated the presence of mutations associated with resistance to NS3 protease inhibitors; however, these studies were limited to GT1 and GT3 ( [7,8,9]. In the patients studied, we found the V170I mutation associated with resistance to NS3 protease inhibitors in three patients, of whom two were infected with GT4a+GT4o and one with GT4a.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, Even fewer data are available on the presence of naturally occurring RAS and their possible impact on the response to treatment with direct-acting antivirals (DAAs). Recently, the natural presence of RASs in the viral genome (NS3, NS5A and NS5B) was associated with a decreased virological response rates to DAA [7][8][9]. This study aimed to characterize the genetic subtypes of HCV-GT4 in Saudi Arabian patients and analyse the prevalence and characteristics of resistance-associated substitutions (RASs) in DAAnaïve patients.…”
Section: Introductionmentioning
confidence: 99%
“…The NS3 protease gene was successfully sequenced in all patients. Several reports demonstrated the presence of mutations associated with resistance to NS3 protease inhibitors; however, these studies were limited to GT 1 and GT 3 [7][8][9]. In the patients studied, we found the V170I mutation associated with resistance to NS3 protease inhibitors in three patients, of whom one was infected with GT 4a, one with GT 4o, and the other one was recombinant virus GT 4a/GT 4o/GT 4a.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, even fewer data are available on the presence of naturally occurring RAS and their possible impact on the response to treatment with direct-acting antivirals (DAAs). Recently, the natural presence of RASs in the viral genome (NS3, NS5A, and NS5B) was associated with a decreased virological response rates to DAA [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Andrade and cols. observed substitutions in the amino acid positions 168 (D168A/G/T) and 122 (S122G) in a group of few therapy-naïve patients (Andrade et al, 2020). Another study found a variety of RAVs in the NS3 region: S122G/N; G122S/T/N; and I170V in a group of patients infected with HCV-1 (Aguiar et al, 2020).…”
Section: Discussionmentioning
confidence: 96%